Impact of cathode biofouling in microbial fuel cells and mitigation techniques. (August 2022) - Kolajo, Oluwafemi Oladipupo; Pandit, Chetan; Thapa, Bhim Sen; Pandit, Soumya; Mathuriya, Abhilasha Singh; Gupta, Piyush Kumar; Jadhav, Dipak A.; Lahiri, Dibyajit; Nag, Moupriya; Upadhye, Vijay Jagdish
Abstract: The unwanted biofilm development on the surface of the cathode in microbial fuel cell (MFC) may hinder the transfer of protons, thereby limiting the transfer of the protons into the cathodes. Cathode biofouling is one of the major drawback impairing the use of MFC to a larger extent for energy generation. Numerous attempts are been made to overcome this and improve the performance in MFC. Extensive research has been done in recent times to tackle biofouling of cathode and minimize these losses and make this technology practically applicable. This review focuses on the effect of biofouling on the cathode material in MFC. The article deeply provides the basic principles of microbial mediated fouling on cathode and highlights the details of biofouling of cathode in an MFC vis-à-vis research that are been conducted across globe. Graphical abstract: Image 1